STRATEGI SEKOLAH DALAM PENGUATAN PENDIDIKAN KARAKTER BAGI SISWA DENGAN MEMAKSIMALKAN PERAN ORANG TUA - Wulandari, Yeni; Kristiawan, Muhammad (Graduate Program Magister Manajemen Pendidikan, 2017)
Parents have an important role in shaping and developing the character of children. Therefore, the school should be able to create a good collaboration with parents in fostering the studentsâ characters. This study aimed at finding out how the school applied the strategy to strenghten the studentsâ character in maximizing the role of parents. This research was conducted at SD Negeri 62 of Palembang. The type of this research was qualitative descriptive research. The data were collected through interviews, observation, and documentation. The results of this study suggested that the roles of parents in strenghtening the studentsâ characters were: (1) improving the charactersâ value as part of the formulation of vision, mission and objectives of the institution which were implemented in daily lives. (2) maintaning the strong relationships in strengthening the studentsâ characters, (3) preparing the teachers who had high responsibility in doing their tasks for the success of the students, (4) creating the safe, comfortable and condusive condition which could stimulate character education, and maintaining the Islamic environment in worship, work and social interaction. The results of the implementation of the character building program in SD Negeri 62 Palembang were as follows: (1) learners were accustomed to say greetings, (2) students had tolerance and mutual respect among fellow students, (3) students were honest, (4) students were polite, (5) students were highly integrated, and (6) the students concerned on their environment.